Frequency of Tea Consumption among Iron Deficient Pregnant Women - Khairunnisa, Nazneen Hameed, Naeem Ahmed Khan, Mahgul Hameed (Pakistan Journal of Medical & Health Sciences, 2022)
Anemia in pregnancy is a fundamental problem that affects not only the life of the mother, but also the life of the child. Iron deficiency has become one of the most important public health problems, and its prevalence is rising in both developing and developed countries. Objective: To determine the frequency of tea consumption by pregnant women with iron deficiency. Study Design: A Cross-sectional study. Place and Duration: The study was held in the Department of Obstetrics and Gynecology of the Aga Khan University Hospital (AKUH), Karachi for six months from 26th October 2020 to 26th April 2021. Methods: Data were collected prospectively after oral consent was obtained from the patients. 145 patients meeting the inclusion criteria were included in the study. Simple descriptive statistics like mean and standard deviation are used to depict quantitative data, whereas frequency and percentage are used to represent qualitative characteristics. To examine the impact of effect modifiers on the outcome variable, stratification was done. A chi-square test was employed after stratification, and a p value of <0.05 was deemed significant. Results: A total of 145 pregnant patients were enrolled in the study. In our study, the mean age and gestational age were 32.26±8.74 years and 18.45±4.22 weeks. 912 (63.24%) and 53 (36.86%) of 145 pregnant women with iron deficiency anemia consumed tea and did not drink it. Conclusion: This study suggests that tea consumption is quite common in our society and plays an important role in iron deficiency anemia. In light of the test results, prompt identification and treatment are recommended. Keywords: Pregnancy, Iron deficiency anemia, Tannin levels and Tea consumption.